2022
DOI: 10.3389/fmicb.2022.966264
|View full text |Cite
|
Sign up to set email alerts
|

Viability droplet digital polymerase chain reaction accurately enumerates probiotics and provides insight into damage experienced during storage

Abstract: Probiotics are typically enumerated by agar plate counting (PC) techniques. PC has several limitations including poor specificity, high variability, inability to enumerate dead cells, viable but non-culturable cells and cells in complex matrices. Viability droplet digital polymerase chain reaction (v-ddPCR) is an emerging enumeration technique with improved specificity, precision, and the ability to enumerate cells in varying states of culturability or in complex matrices. Good correlation and agreement betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Digital PCR (dPCR) is a third-generation PCR and an emerging technology for microbial quantification (Agrimonti et al, 2019;Kiefer et al, 2022). Unlike qPCR, dPCR does not require standard curves for absolute quantification, and its sample preparation and amplification confirmation methods are different (Salipante and Jerome, 2020).…”
Section: Digital Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital PCR (dPCR) is a third-generation PCR and an emerging technology for microbial quantification (Agrimonti et al, 2019;Kiefer et al, 2022). Unlike qPCR, dPCR does not require standard curves for absolute quantification, and its sample preparation and amplification confirmation methods are different (Salipante and Jerome, 2020).…”
Section: Digital Pcrmentioning
confidence: 99%
“…Poisson statistics based on comparing the number of positive (with signal fluorescence) and negative reactions is used to determine the absolute quantity of the target sequence (Hansen et al, 2020;Salipante and Jerome, 2020). Like normal qPCR, dPCR cannot distinguish between live and dead cells; hence, it is coupled with viability dyes for selective quantification of live cells (Kiefer et al, 2022). Studies have reported the application of dPCR methods for quantification of Bifidobacterium spp.…”
Section: Digital Pcrmentioning
confidence: 99%